The central neural organization of cardiovascular control - Ciriello, John; Caverson, Monica M.; Polosa, C. (Canio); ScienceDirect eBooks; Symposium on Function of the Ventrolateral Medulla in the Control of the Circulation (1988 : London, Ont.) (Amsterdam ; New York : Elsevier, 1989)
The Satellite Symposium of the 18th Annual Meeting of the Society for Neuroscience, "Function of the Ventrolateral Medulla in the Control of the Circulation", held in London, Ontario, Canada, Nov. 11-13, 1988, focused on the newest research developments into the central neural organisation of cardiovascular control. The central nervous system is vital in the controlling of arterial pressure via the regulation of sympathetic and parasympathetic nervous discharge to blood vessels and the heart. The central nervous system also controls the release of hormones that regulate the circulation and couple the circulatory system to different behaviours. This volume concentrates on the most recent experimental advances in the neurosciences. Current research disproves the concept of a vasomotor medullary centre, suggesting instead that the control of sympathetic preganglionic activity occurs via neural pathways. The pathways of greatest significance are proposed to originate from neurons located on, or close to, the ventral surface of the medulla oblongata. The proceedings of this symposium represent an important breakthrough in neuroscientific research. An indispensable resource book.
Includes bibliographical references and index.
Online resource; title from publisher's Web site (ScienceDirect, viewed on June 18, 2012).
Elsevier
Keywords: Blood -- Circulation -- Regulation -- Congresses; Vasomotor system -- Congresses; Medulla oblongata -- Congresses; Neurotransmitters -- Research -- Congresses; Blood -- Circulation -- Regulation; Medulla oblongata; Vasomotor system; Electronic books